(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Mobile Learning We operate as a global society, so we carry our smartphones with us wherever we go. In between conversations, we look down and focus our minds on what we think is necessary or interesting. So, education, at least in the most necessary aspects, should be there. It accompanies us on our travels, in our whims, in our desires. If our laptops are with us all over the world, education will be with us through technology. Online learning - A popular trend in the education list today is online learning. Blended learning - Since the development of technology, blended learning has never left the list of popular education trends. With this method, you can use both face-to-face and distance learning methods. Thanks to this, students become the center of learning. At the same time, teachers take on the role of mentors to guide students. This modern trend not only enhances students’ learning experience, but also awakens their motivation to learn.